TOPICAL ISSUES OF THE ANALYTICAL PROCEDURES OF FINANCIAL ANALYSIS INDICATORS OF FINANCIAL STATEMENTS - E. Shapoval (Вестник университета)
The article highlighted and justified the problem - commonality of a number of available techniques of financial analysis. Proposed indicators to assess the solvency and financial stability, taking into account the impact of the industry. It analyzes the financial instruments of financial analysis.